2018
DOI: 10.1142/s0218127418500554
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistencies in Numerical Simulations of Dynamical Systems Using Interval Arithmetic

Abstract: Over the past few decades, interval arithmetic has been attracting widespread interest from the scientific community. With the expansion of computing power, scientific computing is encountering a noteworthy shift from floating-point arithmetic toward increased use of interval arithmetic. Notwithstanding the significant reliability of interval arithmetic, this paper presents a theoretical inconsistency in a simulation of dynamical systems using a well-known implementation of arithmetic interval. We have observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…These and other problems were recently analyzed in several studies on computational chaos. 2932 It has been shown that one of the ways of reducing these drawbacks is through the arithmetic interval technique. 31 Nevertheless, we developed some algorithms of arbitrary precision created exclusively for the modified logistic map x n + 1 = r x n ( 1 x n ) + P .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These and other problems were recently analyzed in several studies on computational chaos. 2932 It has been shown that one of the ways of reducing these drawbacks is through the arithmetic interval technique. 31 Nevertheless, we developed some algorithms of arbitrary precision created exclusively for the modified logistic map x n + 1 = r x n ( 1 x n ) + P .…”
Section: Methodsmentioning
confidence: 99%
“…2932 It has been shown that one of the ways of reducing these drawbacks is through the arithmetic interval technique. 31 Nevertheless, we developed some algorithms of arbitrary precision created exclusively for the modified logistic map x n + 1 = r x n ( 1 x n ) + P . This allowed us to eliminate any problem of chaos degradation from our computational simulations using thousands of significant digits as needed without a relevant computational cost.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our approach is based in a generalization of the one‐step matrix method developed by Demidovich and other authors 1–3 some time ago, valid for systems of the form boldyfalse(tfalse)=Afalse(tfalse)boldyfalse(tfalse). One clear presentation of this method appears in the textbook by Farkas, 4 and it is interesting to compare it with some related procedures; see for instance previous studies 5,6 . It is quite important to remark that, while the Demidovich matrix method is applied to linear equations (with variable coefficients), our matrix method is a generalization to nonlinear systems.…”
Section: Introductionmentioning
confidence: 99%